On the relevance of local–distortional interaction effects in the behaviour and design of cold-formed steel columns. (November 2015) - Martins, A.D.; Dinis, P.B.; Camotim, D.; Providência, P.
Highlights: Relevance of web-triggered L–D interaction in cold-formed steel columns investigated. Numerical results concerning lipped channel, hat, zed and rack-section columns presented. Two quite different types of L–D mode interaction are identified and characterised. Development/calibration of DSM-based design approaches against L–D interactive failures. Use of numerical/experimental ultimate strengths to assess the DSM design approach merits. Abstract: The paper reports the results of a numerical investigation on the relevance of web-triggered local–distortional interaction on the ultimate strength of a large number of cold-formed steel fixed-ended (plain) lipped channel, zed, hat and rack-section columns. These results concern columns with various geometries (cross-section dimensions and unrestrained length) and yield stresses, ensuring a wide variety of combined ratios between the (i) distortional and local critical buckling stresses ( RDL ) and (ii) yield and non-critical buckling stresses ( Ry ). To avoid interaction with global buckling, all columns have global critical buckling stresses much higher than their local, distortional and yield counterparts. The aim of this study is to identify combinations of these ratios for which L–D interaction is relevant, in the sense that it affects visibly the column elastic and elastic–plastic post-buckling behaviours, ultimate strength and failure mechanism – special attention is devoted to the ultimate strength erosion. The numerical ultimate strength data obtained are then compared with the predictions of (i) the currently codified DSM (Direct Strength Method) strength curves for the design of columns failing in local and distortional modes and (ii) available DSM-based design approaches specifically developed to handle local–distortional interactive failures. Then, experimental results available in the literature concerning lipped channel and rack-section columns failing in local–distortional interactive modes are used to assess the quality of the estimates provided by the DSM-based design approaches. Finally, the paper closes with some considerations on the design of cold-formed steel columns undergoing L–D interaction.